Bērnu literatūra "atkušņa" sākumā (laikraksta "Sovetskaja molodjož" materiāli, 1953.-1955. gadi). - Vaļejeva, Jekaterina (Latvijas Universitāte, 2016)
Šis pētījums ir vēltīts bērnu daiļliteratūras analīzei laikrakstā «Sovetskaja Molodjož» laika posmā no 1953. līdz 1955. gadam. Darbā ir pētītas un analizētas periodiskā izdevuma īpatnības rakstos, kuru mērķauditorija ir bērni. Pētījumā tiek izskatītas arī problēmas, kuras saistītas ar «atkušņa» perioda sākuma literatūru. Darba praktiskajai daļai tika izmantoti 1953.-1955. gadu laikraksta «Sovetskaja Molodjož» raksti. Darbu var izmantot periodisko izdevumu daiļliteratūras un tās vēstures pētnieki un visi interesenti.

The study focuses on the analysis of children's literature in the newspaper «Sovetskaya molodjozh» in the period from 1953 to 1955 years. The paper identified and analyzed the characteristics of the periodical in terms of texts aimed at children's readership. The study also deals with the problems related to the literature of the beginning of the period of the «thaw». The practical material for analysis were the numbers of the newspaper «Sovetskaya molodjozh» for the period of 1953-1955 years. The work would be interesting for researchers of fiction within periodicals, as well as for all interested in the history of children's literature.
Children Literature at the Beginning of the "Thaw": The Materials of the Newspaper "Sovetskaya molodjozh" in 1953-1955.
Keywords: Filoloģija; «Советская молодежь»; детская литература; «оттепель»; русская литература Латвии